Ransum Puyuh Petelur yang Mengandung Bungkil Inti Sawit sebagai Pengganti Bungkil Kedelai Berbentuk Pellet Ditinjau dari Sifat Fisik dan Nutrisi - Anwar Efendi Harahap; Khoirunnisa Khoirunnisa; Jully Handoko (Fakultas Peternakan, Universitas Padjadjaran, 2020)
This study aimed to evaluate the physical and nutritional of laying quail diets containing palm kernel cake (PKC) as a substituted for soybean cake in the form of pellets. The research used a completely randomized design with 4 x 2 factorial with 2 replication. Factor A consisting of A0 = Soybean meal 30% + Palm kernel cake 0%; A1 = Soybean meal 20% + Palm kernel cake 10%; A2 = Soybean meal 10% + Palm kernel cake 20% ; A3 = Soybean meal 0% + Palm kernel cake 30% and factor B which consists of B1 = 5% molasses, B2 = 10%. The parameters measured were the physical content of pellets (moisture content, density, stack angle, pile density, pile compaction density) and pellet nutrition (dry matter, crude protein and crude fiber). The results showed that there was an interaction between substituted soybean meal with palm kernel meal by 30% with the addition of 10% molasses which gave the best physical and nutritional of pellets the density, crude protein and crude fiber